Conspicuity of malignant pleural mesothelioma in contrast enhanced MDCT – arterial phase or late phase? - Lukas Luerken; Philipp Laurin Thurn; Florian Zeman; Christian Stroszczynski; Okka Wilkea Hamer (BMC Cancer, 2021)
Abstract Background To determine if late phase is superior to arterial phase intraindividually regarding conspicuity of MPM in contrast enhanced chest MDCT. Methods 28 patients with MPM were included in this retrospective study. For all patients, chest CT in standard arterial phase (scan delay ca. 35 s) and abdominal CT in portal venous phase (scan delay ca. 70 s) was performed. First, subjective analysis of tumor conspicuity was done independently by two radiologists. Second, objective analysis was done by measuring Hounsfield units (HU) in tumor lesions and in the surrounding tissue in identical locations in both phases. Differences of absolute HUs in tumor lesions between phases and differences of contrast (HU in lesion – HU in surrounding tissue) between phases were determined. HU measurements were compared using paired t-test for related samples. Potential confounding effects by different technical and epidemiological parameters between phases were evaluated performing a multiple regression analysis. Results Subjective analysis: In all 28 patients and for both readers conspicuity of MPM was better on late phase compared to arterial phase. Objective analysis: MPM showed a significantly higher absolute HU in late phase (75.4 vs 56.7 HU, p < 0.001). Contrast to surrounding tissue was also significantly higher in late phase (difference of contrast between phases 18.5 HU, SD 10.6 HU, p < 0.001). Multiple regression analysis revealed contrast phase and tube voltage to be the only significant independent predictors for tumor contrast. Conclusions In contrast enhanced chest-MDCT for MPM late phase scanning seems to provide better conspicuity and higher contrast to surrounding tissue compared to standard arterial phase scans.